Pelatihan Pembuatan Eco-Enzyme Untuk Peningkatan Pengetahuan Siswa SMKN Bikomi Selatan - Made Santiari; Hernur Yoga Priyambodo; Anggi Jayadi Riwu; Maria Imaculata Aton (UNIB Press, 2023)
North Central Timor is one of the banana-producing areas that produces banana peel waste. Banana peels can be used as an eco-enzyme, where the manufacturing process needs to be socialized to SMKN students who will take part in internships as additional knowledge. This service aims to increase students' knowledge regarding the manufacture of eco-enzymes. This service was carried out at SMKN Bikomi Selatan for two days face to face with an interval of one week. The first day of service was filled with making eco-enzymes and a week later it was filled with observing the eco-enzymes that had been made and filling out questionnaires by service participants. The eco-enzyme product produced after a week of storage is milky white, has a fermented smell and there is foam when opened. Seventy-three point thirty-three percent of respondents agreed that the media and methods of service were appropriate.